2014
DOI: 10.1093/rfs/hhu042
|View full text |Cite
|
Sign up to set email alerts
|

Peer Effects in Risk Aversion and Trust

Abstract: Existing evidence shows that risk aversion and trust are largely determined by environmental factors. We test whether one such factor is peer influence. Using random assignment of MBA students to peer groups and predetermined survey responses of economic attitudes, we find causal evidence of positive peer effects in risk aversion and no effects in trust. After the first year of the MBA program, the difference between an individual and her peers' average risk aversion has shrunk by 41%. Finding no peer effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(58 citation statements)
references
References 88 publications
1
57
0
Order By: Relevance
“…For peer effects, Manski (1993Manski ( , 2000 delineates three sources of potential similarity in observed behavior: (1) endogenous peer effects, where an individual's behavior varies with the observed behaviors (such as actions or outcomes) of the group; (2) contextual peer effects, where an individual's behavior varies with the exogenous characteristics of the group; and (3) correlated effects, where individuals within a group behave similarly because they endogenously select peers who are similar to themselves or because they all face similar institutional environments. Ahern et al (2014) further distinguish the three peer effects. The correlated effects lead to a similarity in the outcomes of individuals and peers but do not reflect social interactions.…”
Section: Plan Demographics and Participant Contribution Behaviormentioning
confidence: 95%
See 1 more Smart Citation
“…For peer effects, Manski (1993Manski ( , 2000 delineates three sources of potential similarity in observed behavior: (1) endogenous peer effects, where an individual's behavior varies with the observed behaviors (such as actions or outcomes) of the group; (2) contextual peer effects, where an individual's behavior varies with the exogenous characteristics of the group; and (3) correlated effects, where individuals within a group behave similarly because they endogenously select peers who are similar to themselves or because they all face similar institutional environments. Ahern et al (2014) further distinguish the three peer effects. The correlated effects lead to a similarity in the outcomes of individuals and peers but do not reflect social interactions.…”
Section: Plan Demographics and Participant Contribution Behaviormentioning
confidence: 95%
“…Ahern et al. () further distinguish the three peer effects. The correlated effects lead to a similarity in the outcomes of individuals and peers but do not reflect social interactions.…”
Section: Plan Demographics and Participant Contribution Behaviormentioning
confidence: 99%
“…Similarly, there may be selection in the sorting of adolescents into classes (due to geographic proximity, family background, and so forth), either by parental or school influence on class assignment (see, inter alia, Jackson and Rogers (2007) for evidence on social sorting processes). Secondly, attending the same class or friendship may result in convergence in risk preferences over time (Ahern et al, 2014). The objective of this paper is not to differentiate betweeen friends' assortative matching (or selective sorting into classes) and subsequent convergence in preferences as relations deepen.…”
Section: Assortative Matching On Risk and Loss Preferencesmentioning
confidence: 99%
“…In a recent study, Ahern et al (2014) showed in a sample of MBA students that peer effects lead to a convergence of risk attitudes over the course of one academic year. We find different results.…”
mentioning
confidence: 99%
See 1 more Smart Citation